The summer precipitation response of latewood tree‐ring chronologies in the southwestern United States. (19th January 2021) - Howard, Ian M.; Stahle, David W.; Torbenson, Max C. A.; Griffin, Daniel
Abstract: Latewood width tree‐ring chronologies from arid‐site conifers in the southwestern United States are correlated with precipitation during portions of the summer monsoon season. The onset date and length of the monsoon season varies across the region, and these regional differences in summer rainfall climatology may impact the strength and timing of the warm season precipitation response of latewood chronologies. The optimal latewood response to summer precipitation is computed on a daily basis using 67 adjusted latewood chronologies (LWa) from the southwestern United States, adjusted to remove correlation with preceding earlywood growth. Most LWa chronologies are significantly correlated with precipitation summed over a period of approximately 4 weeks (29 days) in early summer. This early summer precipitation signal is present in most ponderosa pine chronologies across the study area. It is also evident in Douglas‐fir chronologies, but only from southern Arizona and New Mexico. The Julian date of summer precipitation onset increases from south to north in the instrumental precipitation data for the southwestern United States. The timing of the early summer season precipitation response in most LWa chronologies also tends to occur later in the summer from southeastern Arizona into northern New Mexico and eastern Colorado. Principal components analysis of the LWa chronologies reproduces two of the three most important spatial modes of early summer precipitation covariability seen in the instrumental data. The first PC of LWa is related to the same atmospheric circulation features associated with PC1 of instrumental early summer precipitation, including cyclonic circulation over the southwestern United States and moisture advection from the eastern Pacific. Correlation analyses between antecedent cool season precipitation and early summer rainfall using instrumental and tree‐ring reconstructed precipitation indicates that the tree‐ring data reproduce the multi‐decadal variability in correlation between seasons seen in the instrumental data. Abstract : Latewood width tree‐ring chronologies from the southwestern United States have been a useful proxy for reconstructing summer precipitation. However, the onset and importance of summer rains varies across the region, and this appears to affect the optimal latewood growth response to moisture. Using daily precipitation data, this study demonstrates that latewood width tree‐ring chronologies from the southwestern United States are correlated with early summer precipitation, and the optimal growth response appears to track the northward migration of the monsoon season.